1998
DOI: 10.1016/s0378-1097(98)00052-4
|View full text |Cite
|
Sign up to set email alerts
|

Vi-deficient and nonfimbriated mutants of Salmonella typhi agglutinate human blood type antigens and are hyperinvasive

Abstract: We generated nonfimbriated mutants from both Vi-positive and -negative Salmonella typhi to analyze the role of type 1 fimbriae and Vi-antigen in bacterial invasion. A Vi-defective mutant of S. typhi GIFU 10007-3 was more invasive than the wild-type strain GIFU 10007. The wild-type strain expressing Vi-antigen did not agglutinate both Saccharomyces cerevisiae and human erythrocytes but Vi-defective mutants were able to agglutinate S. cerevisiae and human erythrocytes. Nonfimbriated mutants from Vi-negative GIFU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…Consistent with a previous report (Miyake et al, 1998), we found that the DviaB mutant (STY2) was more invasive for T84 cells than the S. Typhi wild-type strain (Ty2) (12-fold increase) when cells were grown under conditions optimal for expression of the Vi antigen and bacterial entry was assessed using a gentamicin protection assay (Fig. 4B).…”
Section: Reduction Of Il-8 Secretion By Human Epithelial Cells Is VI supporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with a previous report (Miyake et al, 1998), we found that the DviaB mutant (STY2) was more invasive for T84 cells than the S. Typhi wild-type strain (Ty2) (12-fold increase) when cells were grown under conditions optimal for expression of the Vi antigen and bacterial entry was assessed using a gentamicin protection assay (Fig. 4B).…”
Section: Reduction Of Il-8 Secretion By Human Epithelial Cells Is VI supporting
confidence: 92%
“…An alternative mechanism by which the viaB locus may inhibit IL-8 production is that the Vi-capsular antigen physically masks TLR ligands on the bacterial cell surface or acts as a physical barrier to their release. The finding that the Vi antigen blocks agglutination of S. Typhi with anti-LPS serum and inhibits yeast agglutination mediated by type 1 fimbriae (Miyake et al, 1998) supports the idea that the Vi capsule can physically mask surface structures. Finally, the viaB locus encodes the TviA regulatory protein that may prevent IL-8 expression in epithelial cells by altering expression of bacterial genes other than those located in the tviABCDEvexABCDE operon.…”
Section: Introductionmentioning
confidence: 56%
“…These data suggest that Typhi survives and replicates within phagocytic cells of the bone marrow, spleen, and liver, but the genetic basis of this capability remains largely unknown. The expression of a capsular polysaccharide, the Vi antigen, appears to be crucial for Typhi to survive in mouse and human macrophage cell lines and to resist to lysis by serum complement [65][66][67], whereas it does not appear to be necessary for epithelial cell invasion [68]. This antigen is also known to be associated with the virulence of the organism in i o and to confer immunity against typhoid fever, when injected alone, in areas with a high incidence of this disease [69,70].…”
Section: Typhimentioning
confidence: 99%
“…There has been no uniform implementation of the ViPS vaccine with a wide enough coverage and for a sufficient period of time to substantiate this theory. Additionally, while Vi-deficient strains of Salmonella typhi have been proven to be hyperinvasive in ex vivo conditions, via an increase in secreted bacterial proteins [22], the negligible incidence of typhoid fever caused by this strain suggests a decreased ability to survive once in the blood stream.…”
mentioning
confidence: 99%